2021
DOI: 10.21203/rs.3.rs-1031840/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal Changes and Decrease of Suicides and Suicide Attempts in France Over the Last 10 Years”.

Abstract: Introduction: The objective of this study was to examine the evolution of suicides and suicide attempts over the last 10 years in France. Methods: We analyzed the number of deaths by suicide and suicide attempts in metropolitan France (2009-2018) from French national databases, on a daily, weekly or monthly basis. Seasonal variation in suicide rates was modeled using a cosinor function. Based on this model, we determined the association of suicides and suicide attempts with geographic characteristics, age, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…This may be attributed to seasonal fluctuations, as the study took place during autumn and spanned a one-month duration. During this period, the day length was reduced by over two hours and the average temperature dropped by 8 • C. There is a growing body of evidence suggesting that seasonality can impact both biochemistry and cognitive measures [41,42]. Specifically, other studies have reported decreased serotonin levels among control groups during the autumn to winter transition, as observed in our study [43,44].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This may be attributed to seasonal fluctuations, as the study took place during autumn and spanned a one-month duration. During this period, the day length was reduced by over two hours and the average temperature dropped by 8 • C. There is a growing body of evidence suggesting that seasonality can impact both biochemistry and cognitive measures [41,42]. Specifically, other studies have reported decreased serotonin levels among control groups during the autumn to winter transition, as observed in our study [43,44].…”
Section: Discussionsupporting
confidence: 67%
“…The signal was divided into periods of 1 s duration; periods with a signal amplitude above 100 µV were excluded. The spectral bands used for further signal processing were delta (0.5-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), beta-1 (12-18 Hz), beta-2 (18-30 Hz), and gamma (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Hrv and Biochemical Parametersmentioning
confidence: 99%